Hematological ratios as markers of lupus activity in Paraguayan patients with systemic lupus erythematosus - Morel, Zoilo; Acosta, Rodrigo; Paats, Astrid; Cabrera Villalba, Sonia; de Abreu, Paloma; Avila Pedretti, Gabriela; Centurion, Osmar Antonio; Acosta, María Eugenia; Martinez de Filartiga, María Teresa; Fuentes Silva, Yurilis; Acosta Colman, Isabel (Medicina Clínica y Social, 2024)
Introduction: The neutrophil/lymphocyte ratio (NLR) and the platelet/lymphocyte ratio (PLR) are markers of inflammation and prognosis in systemic diseases. This study determined the association between hematological indices, and disease activity in patients with systemic lupus erythematosus (SLE). Methods: This prospective, observational and analytical cross-sectional study included 87 Paraguayan patients diagnosed with SLE, according to the ACR/EULAR 2019 criteria. We investigate four hematological indices: neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), eosinophil/lymphocyte ratio (ELR), and monocytes/lymphocyte ratio (MLR). Results: Eighty-seven percent were female, with a median age of 34.9 ±12.3 years. SLEDAI mean of 3.68 ± 4.76 was found. SLEDAI mean was 3.68 ± 4.76. Positivity of anti-DNAds was found in 52% of the patients. CRP mean was 3.5 ± 4.6. Regarding values of hematological indices, we found: NLR mean of 2.4 ± 1.6 was obtained, ELR 0.07 ± 0.09, MRL 0.07 ± 0.07 and PLR 155.89 ± 80.69. A significant positive correlation was found with SLEDAI and NLR (r=0.34, p=0.001). Based on the ROC curve, the best cut-off value for our patient cohort capable of predicting patients with high activity is for NLR values ? 2.283 (AUC: 0.66). Conclusion: NLR could be a valuable and accessible biomarker to identify elevated activity in patients with SLE.